Respuesta:
✨[tex]\huge{\blue{\tt{Hola}}}[/tex]✨
Explicación paso a paso:
a) 10/(20-10) + 4 =5
[tex] \frac{10}{20 - 10} + 4 \\ 10 \div 10 = 1 \\ 1 + 4 = 5[/tex]
b) -5(-9 + 3 x 4) - 6 =-21
[tex] - 5 \times ( - 9 + 12) - 6 \\ - 5 \times 3 - 6 \\ - 15 - 6 \\ - 21[/tex]
c)-(3-4÷4) + 3(2-6)=-14
[tex] - (3 - 1) + 3 \times (2 - 6) \\ - 2 + 3 \times ( - 4) \\ - 2 - 3 \times 4 \\ - 2 - 12 \\ - 14[/tex]
d) -3[4 +5(-3+ 4)] + 2[64(6-2)] =485
[tex] - 3 \times (4 + 5) + 2 \times (64 \times 4) \\ - 3 \times 9 + 2 \times (64 \times 4) \\ - 27 + 2 \times 256 \\ - 27 + 512 \\ 485[/tex]
e) 2 + 5{4- [5+ (1+2+2)]} =-28
[tex]2 + 5 \times (4 - (5 + 5)) \\ 2 + 5 \times (4 - 10) \\ 2 + 5 \times ( - 6) \\ 2 - 5 \times 6 \\ 2 - 30 \\ - 28[/tex]
f) -{-3+ [-7(6-5) + 2 x 3]} - [-6(2-3)] =-2
[tex] - ( - 3 + (7 + 2 \times 3)) - ( - 6 \times ( - 1)) \\ - ( - 3 + ( - 7 + 6)) - 6 \\ - ( - 3 - 1) - 6 \\ - ( - 4) - 6 \\ 4 - 6 \\ - 2[/tex]